Pattern of Smart Phone and Internet Usage among Medical Students in Surat, Gujarat - A Cross Sectional Study - Rahul B Damor; Sukesha P Gamit; Anjali Modi; Jayant Patel; J K Kosambiya (Medsci Publications, 2018)
Background: Advent of mobile and internet has been most impor- tant technological advancement of the century. About 60 percent of internet users in India access internet via their smart phones. Objective: To study the pattern of smart phone, internet usage, its perception and addiction among medical students. Methods: Cross-sectional study, conducted among medical stu- dents of Government Medical College, Surat. A semi-structured proforma along with Young's Internet Addiction scale was used. Results: Of 313 participants, 51.4% were male & 48.6% were fe- male. Majority of them were using smart phone. Majority were us- ing internet on smart phone. Social networking (65.2 %) was the most common purpose, 53.7 % using internet for 1 to 3 hours daily. About (48.6 %) felt addicted to internet. Porn was watched by 34.8 % on mobile; while 11.2 % feels addicted to watching porn material. According to Young's Internet Addiction scale, 59.1 % average online users, 23.3 % less than average online users, 17.3 % possible addict and 0.3 % addicted to internet. Conclusion: Although some participants were using smartphone for academic literature search, majority were using it for social networking. About half of the participants felt addicted to internet.